(untitled) (Biological Sciences - PJSIR, 2022)
An experiment was conducted for a period of 10 weeks to compare the effect of planting density on the growth and yield of Indian spinach (Basella alba) and Nile tilapia (Oreochromis niloticus) in a re- circulating aquaponics system. Indian spinach was planted at four densities (4 plants/m2, 8 plants/m2, 12 plants/m2 and 16 plants/m2). Stocking density of Nile tilapia (Av. body wt. 32.5 g) was 45 fish/tank (water capacity 300 L) in all planting densities. The highest weight gain, percent weight gain, specific growth rate and protein efficiency ratio of fish were obtained at planting density of 12 plants/m2. Feed conversion ratio was also lowest at this density. Number of leaves per plant, plant length, plant weight and yield of Indian spinach were the highest at 12 plants/m2. It was concluded that the plant density of 12 plants/m2, for Indian spinach integrated with 45 fish/tank was suitable for production of both vegetable and Nile tilapia in a recirculating aquaponics system.